Impact of the upgraded version of German“industrial 4 platform”on China's manufacturing industry - Siwei YANG (Dianxin kexue)
Firstly,the organizational structure and positioning of German“Industrial 4 Platform”were introduced,and then the core research was focused on,such as research and innovation,reference system and standardization,network system security.Finally,we should draw on the advanced experience of German manufacturing field,and promote the development of intelligent manufacturing in China.